Perancangan Model Peningkatan Kapasitas Sumber Daya Manusiadi Bank Perkreditan Rakyat (BPR) - Sayekti, Andita; Kartika, Lindawati (Universitas Brawijaya, Indonesia, 2016)
Abstract: The problem of inefficiency faced by Rural Banks is caused by non optimal humanÂ resource's performance. There are many Rural Banks that have not enough employees, soÂ many employees do double tasks, uncompleted management happened, and low competence-compensations, that obstruct the performance of them. Because of that, the objective ofÂ this research is to map the condition of Rural Banks'human resource based on its qualityÂ and quantity, identify the policy and strategy of Human Resource Development, evaluate theÂ effectiveness of the rules that exist at Rural Banks, and formulate Rural Banks'cooperation'sÂ scheme with others agencies or education institution. This research was held at Jakarta,Â Bandung, Denpasar, Manado, Medan, Surabaya, and Yogyakarta. The methods of this researchÂ were explorative, quantitative description, and qualitative approach, such as fieldÂ survey, purposive random sampling, and focus group discussion.The results are map of RuralÂ Banks'human resource's condition from its distribution and quality, identification of RuralÂ Bank's human resource's problems, recommendation of recruitment and selection system,Â analysis of position based on competency and its standard, recommendation of training,Â curriculum's scheme, recommendation of compensation, and cooperation with others agencies/education institution that provide labor that are ready to be used by Rural Banks.